Imaging after Pancreaticoduodenectomy: How Can the Radiologist Help the Surgeon - Sanjay Chordiya; Binit Sureka; Tashmeen Sethi; Taruna Yadav; Vaibhav Kumar Varshney; Subhash Chandra Soni; Jeewan Ram Vishnoi; Ayushi Agrawal (Indian Journal of Radiology and Imaging)
Pancreaticoduodenectomy is the one of the most complex surgeries done for periampullary pathologies. Computed tomography is the imaging modality of choice in the postoperative period. The radiologist should have the knowledge regarding normal findings and complications that can be encountered postsurgery. This will help in quick decision making and timely management of these complex cases.